2021
DOI: 10.1002/mbo3.1172
|View full text |Cite
|
Sign up to set email alerts
|

Application of a semi‐automatic, intensive follow‐up for improving efficacy and adherence of Helicobacter pylori eradication therapy: A randomized controlled trial

Abstract: A complete understanding and good adherence are crucial for successful Helicobacter pylori eradication. Proper frequency of reminders might be helpful to both doctors and patients to maintain adherence during treatment. The study was to evaluate the influence of an intensive follow‐up system based on a clinical database on H. pylori eradication therapy. A total of 196 eligible patients were equally and randomly divided into an intensive follow‐up group and a control group. Both groups were administered bismuth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 25 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…Two studies 21,24 provided sufficient data for allocation concealment and were judged as low risk, while others were judged as unclear risk. Regarding blinding, 3 studies 20,22,24 described methods for single blinding, one study 27 was open trial (non‐blind), and the remaining 5 studies 21,23,25,26,28 were judged as unclear risk due to insufficient information. With respect to attrition bias, one study conducted by Ma et al 28 was judged as high risk of bias due to the unbalanced proportion of missing data, and all the remaining studies were judged as low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies 21,24 provided sufficient data for allocation concealment and were judged as low risk, while others were judged as unclear risk. Regarding blinding, 3 studies 20,22,24 described methods for single blinding, one study 27 was open trial (non‐blind), and the remaining 5 studies 21,23,25,26,28 were judged as unclear risk due to insufficient information. With respect to attrition bias, one study conducted by Ma et al 28 was judged as high risk of bias due to the unbalanced proportion of missing data, and all the remaining studies were judged as low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8 studies 20,22‐28 (involving 1 875 patients) reported data on H . pylori eradication rate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations